2020
DOI: 10.1080/00913367.2020.1712274
|View full text |Cite
|
Sign up to set email alerts
|

How Downplaying Product Greenness Affects Performance Evaluations: Examining the Effects of Implicit and Explicit Green Signals in Advertising

Abstract: Despite frequent reports that they favor products with environmental benefits, consumers often purchase conventional alternatives. One reason for this is the performance liability associated with green products, in which consumers perceive them as being less effective. This research examines the concept of "green understatement" (i.e., communication of implicit green signals) compared with "green emphasis" (i.e., communication of explicit green signals) in green product advertising as a strategy to enhance per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Instead of an apparent rational appeal of PO, Pakistanis were found more persuaded by the affective appeals IC. For that reason, it supports past green marketing studies conducted in the Asian context that suggested the purchasing decisions of Asian consumers can be influenced by emotional motivational factors such as the “welfare of the nation” [ 6 , 55 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Instead of an apparent rational appeal of PO, Pakistanis were found more persuaded by the affective appeals IC. For that reason, it supports past green marketing studies conducted in the Asian context that suggested the purchasing decisions of Asian consumers can be influenced by emotional motivational factors such as the “welfare of the nation” [ 6 , 55 ].…”
Section: Discussionsupporting
confidence: 79%
“…Research suggests that promoting the usage of such environmentally friendly products can be attained through persuasive tools of communication such as advertising [ 5 , 6 ]. Hence, research on advertisement’s appeals that can persuade the consumption of products manufactured from bio-nanomaterial such as plastics can help to develop effective advertising strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Such information is critical for effectively communicating with targeted consumers. Green product information needs to be clear and meaningful to assist with consumer evaluations (Usrey et al, 2020) and many such companies seek methods to enhance information quality for favourable consumer assessments of their green brands Schmuck et al, 2018). This highlights the need for marketers to understand the information quality associated with green advertisement information, the definition of green information quality and its dimensions in a green advertising context, differences across the dimensions of green information quality and their effects on consumer assessments of green brands.…”
Section: Introductionmentioning
confidence: 99%
“…Such trust in eco-labels also makes the information search less complex (D'Souza et al, 2007) and can improve consumer decision-making (Bickart and Ruth, 2012). Although the multitude of eco-labels in use means that consumers should believe eco-labels to effectively differentiate between alternative green brands (Atkinson and Rosenthal, 2014;Bickart and Ruth, 2012;Usrey et al, 2020). This increases the importance of eco-label credibility [defined as consumer-perceiving eco-labels to certify the product's environmental impact (Goldsmith et al, 2000)].…”
Section: Introductionmentioning
confidence: 99%
“…Not only do consumers perceive green products as more expensive [13], but they also view these products as inferior to non-green product alternatives, thus increasing the amount of usage to achieve the same effect [14]. For these reasons, companies that advertise their green products may experience backfire at the expense of the product's greenness [15]. Furthermore, consumers who care for the environment are less skeptical towards green advertising [16]; however, some environmentally concerned consumers show higher skepticism towards green claims [11,17] despite the fact that they may be unable to distinguish false green claims [18].…”
Section: Introductionmentioning
confidence: 99%